Criticizing Higher Education Policy in Indonesia: Spiritual Elimination and Dehumanisation - Moh. Roqib; Siti Sarah; Agus Husein As Sabiq; Mohamad Sobirin; Abdal Chaqil Harimi (FITK UIN Walisongo, 2021)
The Ministry of Education and Culture's policy on “Merdeka Belajar” (Freedom of Learning) seeks to enable students to master different valuable disciplines to access the work field (link and match). This article investigates Freedom of Learning policy direction and unpacks freedom of learning from the viewpoint of prophetic education theory. This research employs a literature review process. The information was gathered by studying the Ministry of Education and Culture legislation and laws, literature, and compiled references of the policy. The findings suggested that the Freedom of Learning policy's trajectory accommodates data in the material domains (cognitive, affective, and psychomotor), yet it lacked spirituality. The principle of prophetic education is to move humans to be decent (righteous), to achieve the great humans (insān kāmil), and to improve (muṣliḥ) the world into an ideal environment or society (khaira ummah) capable of bridging the gap the means. Professional education continues to carry out a constant, creative mechanism to get citizens closer to God (transcendence) through digitally increasing human ideals and avoiding harmful stuff (liberation). Competence in the policy of independent learning is maintained by prophetic education.